ALLIANCE OF SMALL ISLAND STATES AND ITS ROLE IN SUSTAINABLE ENERGY DEVELOPMENT IN THE SMALL ISLAND DEVELOPING STATES - Debnath, Kankana (PEOPLE: International Journal of Social Sciences, 2019)
The small island developing states (SIDS) are among those nations which are the most underdeveloped and vulnerable in the world. The present climate change (CC) situation is at serious juncture. The amount of carbon and other greenhouse gases (GHG) in the atmosphere are way past the industrial levels ascertained by the United Nations Framework Convention for Climate Change (UNFCCC). It is proved that the developed nations like China, United Nations, Russia are responsible for the maximum emissions and the SIDS has little to no contribution in emissions but are the ones who are the worst affected by the negative effects of CC. As such these nations are very pro climate. They are repeatedly voicing their concerns and appealing the world community to wake up and take proper initiative to control the global warming through AOSIS which is an organizational tool for voicing concerns of the SIDS. The clean energy mechanism is one of the initiatives of the AOSIS which is expected to replace the carbon driven energy production and to sustain the states on their own clean energy and this will be the main key finding of this study along with the prospects of the Initiative for Renewable Island Energy (IRIE). The study will be based on a thorough analysis of the published works of climate experts and personal experience and studies as a climate doctoral scholar. A thorough analytical and empirical process of the issue will be adopted in this study to answer the research questions arising in this study and in the conclusion finding a concrete solution to the problems cited will be attempted.